PERSEPSI MAHASISWA TENTANG PENGELOLAAN PEMBELAJARAN MATA KULIAH DASAR KEAHLIAN (MKDK) - Neti Karnati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
This research is intended to get empirical data on elementary school teacher’s attitude towards children with special needs in the elementary school, DKI Jakarta. The research was held at the department of PGSD (Elementary School Teacher Education), Setia Budi Campus, School of Education of Jakarta (FIP- UNJ), selected sample randomly. The random sample 105 are elementary school teacher doing undergraduate program in basic education. The result shows that teacher’s attitude toward student with special needs have the acceptance limit score for 81.25. This means that any score above the limit score is categorized as positive attitude and score below the limit score is considered as negative attitude. On the cognition aspect, the score is 37.92 meaning teachers have negative attitude towards children with special needs. The score for affection and conation aspect are 26.92 meaning negative attitude too. For the theoretical aspect, the maximum score is 150 whereas the minimum score is 50. Research analysis shows that the maximum empirical score is 146 with the minimum of 88. The average score is 120 meaning that elementary school teachers have positive attitude towards children with special needs.